Does elevation influence the distributional patterns of tropical myxomycetes? A case study in Costa Rica - Rojas Alvarado, Carlos Alonso (2016)
In order to test the hypothesis that elevation may be an important factor accounting for the distribution of myxomycetes in tropical forests, this project was designed and conducted in Costa Rica. Two lower elevational belts were selected for this work due to their floristic and structural resemblance. Using the moist chamber technique, 40 different sites located in four different transects in two different macroclimatic regions were surveyed using three substrates during the rainy and the dry periods of 2014 and 2015. The results showed a lack of differences in diversitybased estimators according to elevation using different approaches and taxonomic differences were found across transects, collecting periods and substrates but not in relation with elevation either. Our results suggest that when increased spatial sampling resolution is implemented and floristic elements are common, elevation may not be as important of a factor in shaping the distribution of myxomycetes in tropical forests as commonly believed.